EARLY DIFFERENTIAL DIAGNOSIS OF THE BRAIN TUMORS WITH HELP OF COMPUTED TOMOGRAPHY - Khoshimov I. G.; Ibragimov S. S,; Madumarova Z. Sh.; Yakubov N. I.; Zulunov A. T. (Web of Journals Publishing, 2024)
Despite the widespread use of modern radiation imaging technologies in the neurosurgical clinic, the problems of diagnosis and treatment of various brain tumors (GM) are still lagging behind in the focus of attention of clinicians and health care organizers. This is due to the prevalence of primary and secondary embolism tumors, a large number of adverse outcomes and the high cost of treating diseases.
Keywords: good quality tumor, bad quality tumor, cranial, instrumental examination.